A Review of Auxin Response Factors (ARFs) in Plants - Li, Si-Bei; Xie, Zong-Zhou; Hu, Chun-Gen; Zhang, Jin-Zhi (Frontiers in Plant Science, 2016)
Auxin is a key regulator of virtually every aspect of plant growth and development from embryogenesis to senescence. Previous studies have indicated that auxin regulates these processes by controlling gene expression via a family of functionally distinct DNA-binding auxin response factors (ARFs). ARFs are likely components that confer specificity to auxin response through selection of target genes as transcription factors. They bind to auxin response DNA elements (AuxRE) in the promoters of auxin-regulated genes and either activate or repress transcription of these genes depending on a specific domain in the middle of the protein. Genetic studies have implicated various ARFs in distinct developmental processes through loss-of-function mutant analysis. Recent advances have provided information on the regulation of ARF gene expression, the role of ARFs in growth and developmental processes, protein–protein interactions of ARFs and target genes regulated by ARFs in plants. In particular, protein interaction and structural studies of ARF proteins have yielded novel insights into the molecular basis of auxin-regulated transcription. These results provide the foundation for predicting the contributions of ARF genes to the biology of other plants.